Influencing Factors of Health Technology Assessment to Orphan Drugs: Empirical Evidence in England, Scotland, Canada, and Australia - Zhou, Na; Ji, Hong; Li, Zheng; Hu, Jun; Xie, Jia-Hua; Feng, Yu-Heng; Yuan, Ni (Frontiers in Public Health, 2022)
Objective: To summarize the intrinsic criteria for the recommendation of rare drugs in the four countries, to try to understand the rationale for the variability in decision-making, and to provide a reference for the establishment of criteria in the process of access to health insurance for rare drugs in different countries and the construction of national uniform criteria. Method：A comparative analysis of 60 HTA guidances of 15 drug-indication pairs appraised by four countries (England, Scotland, Canada, and Australia) from 2017 to 2018, including an in-depth analysis of a case study. Agreement levels were measured using kappa scores. Associations were explored through correspondence analysis. Results: The four countries possess some homogeneity in the assessment, but each has its own preferences. Poor agreement exists between England, Scotland and Canada (-0.410